Advances in nanobiotechnology-propelled multidrug resistance circumvention of cancer. Issue 36 (3rd September 2022) - Chen, Jie; Yu, Xin; Liu, Xinyu; Ni, Jinliang; Yang, Guangcan; Zhang, Kun
Abstract : Multidrug resistance (MDR) is one of the main reasons for the failure of tumor chemotherapy and has a negative influence on the therapeutic effect. Abstract : Multidrug resistance (MDR) is one of the main reasons for the failure of tumor chemotherapy and has a negative influence on the therapeutic effect. MDR is primarily attributable to two mechanisms: the activation of efflux pumps for drugs, which can transport intracellular drug molecules from cells, and other mechanisms not related to efflux pumps, e.g., apoptosis prevention, strengthened DNA repair, and strong oxidation resistance. Nanodrug-delivery systems have recently attracted much attention, showing some unparalleled advantages such as drug targeting and reduced drug efflux, drug toxicity and side effects in reversing MDR. Notably, in drug-delivery platforms based on nanotechnology, multiple therapeutic strategies are integrated into one system, which can compensate for the limitations of individual strategies. In this review, the mechanisms of tumor MDR as well as common vectors and nanocarrier-combined therapy strategies to reverse MDR were summarized to promote the understanding of the latest progress in improving the efficiency of chemotherapy and synergistic strategies. In particular, the adoption of nanotechnology has been highlighted and the principles underlying this phenomenon have been elucidated, which may provide guidance for the development of more effective anticancer strategies.